Alcohol-induced physical intimate partner violence and child development in Peru. (2nd July 2020) - Bedoya, Mariel; Espinoza, Karen; Sánchez, Alan
ABSTRACT: There is limited evidence of the relationship between intimate partner violence (IPV) and child development in developing countries. Alcohol-induced physical IPV (AIPIPV) is one of the main forms of IPV. We use longitudinal data from a cohort of Peruvian children, tracked from the age of 1 year old, to test the association between AIPIPV against the mother during the child's first two years of life, and the child's test scores (vocabulary and math), socio-emotional competencies (self-efficacy and self-esteem, as measured by agency and pride indexes), and delayed school enrolment. Using multivariate regression techniques to estimate the relationship of interest and control for child, household, and community characteristics, we find that early-life exposure to AIPIPV is associated with lower test scores in vocabulary and math, and with lower self-efficacy. No association with self-esteem and with delayed school enrolment is observed.